Outbreak of Ralstonia Mannitolilytica Infection at a Tertiary Care Oncology Center in South India: A Case Series - Ramani, Vinod K.; D.V, Ganesha; Sarathy, Vinu; Bhattacharjee, Somorat; Ganeshan, Shobha; Naik, Radheshyam (Asian Pacific Journal of Cancer Biology, 2021)
Introduction: Ralstonia Mannitolilytica (RM) is a rare opportunistic pathogen capable of causing a serious infection in immunocompromised patients. It is ubiquitous in nature and a frequent contaminant of water supplies. RM infection in cancer patients may have serious implications as they are already susceptible due to underlying malignancy, treatment related immunosuppression, malnutrition and prolonged presence of indwelling central catheters. In this study, we report a case series of RM infection with focus on clinical characteristics, management and patterns of antibiotic sensitivity. Methods: This case series includes 17 cancer patients admitted at Healthcare Global oncology hospital, Bangalore, presenting with fever and/or chills between 22nd February 2020 to 5th May 2020, who had a positive blood culture and/or a chemoport/PICC/central venous catheter (CVC) tip culture positive for RM species. Results: Among all patients, RM was grown from the blood sample of 12 patients having an indwelling chemo-port, 4 patients with PICC line and 1 patient with a central venous line. All patients had a positive blood culture for RM, and two patients had a positive tip culture in their chemo-port and PICC line respectively. Antibiotic treatment includes cefoperazone-sulbactam for 10 patients, ceftazidime for 4 patients, meropenem for 2 patients and ceftriaxone for 1 patient. All 17 patients recovered from the infection without any complications. After 48 hours of incubation, no growth of Ralstonia was reported from any of the current environmental or pharmaceutical water samples. Conclusion: RM may be capable of causing serious infections in cancer patients as they are already immuno-compromised. Furthermore, RM may serve as an effective quality indicator of water and therapeutic supplies. Healthcare professionals should adhere to infection control policies, monitor outbreaks of unusual pathogens and study the emergence of pattern for antibiotic resistance.